Pengaruh Kelebihan Penghasilan Dan Religiusitas Terhadap Intensi Masyarakat Desa Takeranklating Tikung Lamongan Untuk Menjadi Nasabah Di Perbankan Syariah - Dian Mariana Lestari (JES (Jurnal Ekonomi Syariah), 2019)
Sharia bank is a bank which operated by al-Quran and Hadist principle. Completed with MUI intructions therefore when operational process not rely on tire tread. However almost people have a salary and religious background look of that things people sould be make their insentrum to chose sharia bank as a main priority to be the customer. This skripsi entitled ”The influence of salary strength and the religiousity toward the intention of Takeranklating people to be the customer in sharia bank”. This research using quantitative method so answer the research problem about how many the influence of salary strength, and the religiousity in a parsial manner and simultaneous toward people intention in Takeranklating village to be the customer in sharia Bank. This research used quantitative methods with explanation design. This research collect the data used quitionnare and documentation. While data analyze technique used double regression test using parsial and simultaneous test. Result of research showed that the variabel of salary strenght get the positive influence and significant toward people intention of Takeranklating to be a customer in sharia bank with regression coeficient 0,022 scores, score t test is 2,150 scores and the significant is 0,038 scores. While the variabel of religiousity get positive influence and significant toward people intention of Takeranklating to be a customer in sharia bank with regression coefficient 0,622 score, the score of t test is 75,635 scores, and the significant score is 0,000,. While the salary strength and religiousity in a simultaneous manner is significant influence toward people intention of Takeranklating village to be a customer in sharia bank with f test is 2906,753 scores, the significant score is 0,000 scores and f table is 3,10 scores. Keywords: Salary Strength, Religiousity, People Intention